Age, Gender and Common Site of Haematoma Formation among Acute Subdural Hematoma Patients: Experience of 48 Cases in Bangladesh - Uddin, Kalim; Salam, Md Abdus; Haque, Ashraful; Khan, Amir Md; Rahman, Md Mahfuzur; Hussain, Ahmed Riyad; Islam, Rafiqul (Journal of Science Foundation, 2021)
Background: Acute subdural hematoma can occurs in different age group of patients in both male and female. Objective: The purpose of the present study was to observe the age and gender distribution among acute subdural hematoma patients. Methodology: This cross-sectional study was carried out in the Neurosurgery Department of Dhaka Medical College Hospital, Dhaka, Bangladesh from January 2011 to August 2012 for a period of one year and eight months. Patients with acute subdural hematoma who fulfil the inclusion criteria for surgery and got admitted were selected as study population. Acute Subdural hematoma patient of any age, both sex with GCS 5 to 13, thickness of hematoma more than l0 mm, midline shift more than 5 mm, pupil reacting to light and patient presented within 72 hours of injury were included for this study. At admission, a detailed history of the illness was taken from the patient or attendant, thorough general and neurological examinations were carried out and were recorded. Result: A total number of 48 patients were recruited for this current study. The mean age of the patients was 32.39±11.63 years and their age ranged from 10 to 56 years. The male and female ratio was 5:1. Out of 48 patients 17(31.25%) cases were fronto-temporal. Temporo-parietal were 16(33.3%) patients. Fronto-temporo-parietal were 7(14.5%) cases. Parietal were 5(10.41%) cases. Frontal were 3 (6.25%) case. Conclusion: In conclusion majority of the patients are male young adults presented with fronto-temporal and temporo-parietal region of shull. Journal of Science Foundation 2019;17(2):54-57